Robotic-Assisted vs. Open Simple Prostatectomy for Large Prostates: A Meta-Analysis - Xia, Zhongyou; Li, Jinze; Yang, Xiaoying; Jing, Hao; Niu, Chao; Li, Xianhui; Li, Yunxiang; Zhang, Zongping; Wu, Ji (Frontiers in Surgery, 2021)
Purpose: To compare the efficacy and safety of robotic-assisted simple prostatectomy and open simple prostatectomy for large benign prostatic hyperplasia. Methods: We systematically searched the Cochrane Library, PubMed, Embase, and Science databases for studies published through December 2020. Controlled trials on RASP and OSP for large prostates were included. The meta-analysis was conducted with the Review Manager 5.4 software. Results: A total of seven studies with 3,777 patients were included in the analysis. There were no significant differences in IPSS (WMD, 0.72; 95%CI: ‐0.31, 1.76; P = 0.17), QoL (WMD, 0.00; 95%CI: ‐0.39, 0.39; P > 0.99), Qmax (WMD, 1.88; 95% CI: ‐1.15, 4.91; P = 0.22), or PVR (WMD, ‐10.48; 95%CI: ‐25.13, 4.17; P = 0.16) among patients undergoing RASP and OSP. However, compared with patients who underwent OSP, patients who underwent RASP had a shorter LOS (WMD, -2.83; 95%CI: -3.68, -1.98; P < 0.001), less EBL (WMD, -304.68; 95% CI: -432.91, -176.44; P < 0.001), a shorter CT (WMD, -2.61; 95%CI: -3.94, -1.29; P < 0.001), and fewer overall complications (OR, 0.30; 95% CI: 0.16, 0.57; P < 0.001). Nevertheless, RASP was associated with a longer OT (WMD, 59.69, 95% CI: 49.40, 69.98; P < 0.001). Conclusion: The results of the current study demonstrated that RASP had similar efficacy to OSP while maintaining better security. Our findings indicate that RASP is a feasible and effective alternative to OSP.